Weather based operational plant protection on rice hispa and blast of paddy (MAUSAM, 2004)
Studies were made to explore the possibility of control/minimise the damages caused by the rice hispa and blast disease of rice by issuing timely weather based forecast. From the survey conducted by the Department of Plant Protection, Quarantine and Storage (PPQ&S) Faridabad from 1988-93, it was observed that both rice hispa and blast incidences were comparatively more in kharif  than rabi/summer season. Rice hispa appeared more frequently in moderate to severe intensity particularly in Orissa,  Assam, Kerala  and Andhra Pradesh.  Blast disease appeared more in Karnataka, Andhra Pradesh, Orissa, Maharashtra, Madhya Pradesh, Uttar Pradesh.  Drop in maximum (< 32° C) and minimum temperature (< 24.5° C) under humid condition (morning RH > 90%; and afternoon RH > 80%) and cloudy condition was found to be the congenial weather condition for the incidence of rice hispa.  Blast incidences on the crop were found to be favoured by the decrease in minimum temperature (< 23.5° C) in association with increase in morning relative humidity (> 90%) under cloudy condition. The findings of this study validated fairly well with the pest and disease observation made after 1993. It is concluded that forewarning of the incidence of the rice hispa and blast on rice could be possible, well in advance, through Agromet Advisory Service based on the prevailing weather parameters.